Preserved Coronary Flow Reserve Effectively Excludes High-Risk Coronary Artery Disease on Angiography - Naya, Masanao (2014)
Myocardial perfusion imaging has limited sensitivity for the detection of high-risk coronary artery disease (CAD). We tested the hypothesis that a normal coronary flow reserve (CFR) would be helpful for excluding the presence of high-risk CAD on angiography. METHODS: We studied 290 consecutive patients undergoing (82)Rb PET within 180 d of invasive coronary angiography. High-risk CAD on angiography was defined as 2-vessel disease (≥70% stenosis), including the proximal left anterior descending artery; 3-vessel disease; or left main CAD (≥50% stenosis). Patients with prior Q wave myocardial infarction, elevated troponin levels between studies, prior coronary artery bypass grafting, a left ventricular ejection fraction of less than 40%, or severe valvular heart disease were excluded. RESULTS: Fifty-five patients (19%) had high-risk CAD on angiography. As expected, the trade-off between the sensitivity and the specificity of the CFR for identifying high-risk CAD varied substantially depending on the cutoff selected. In multivariable analysis, a binary CFR of less than or equal to 1.93 provided incremental diagnostic information for the identification of high-risk CAD beyond the model with the Duke clinical risk score (>25%), percentage of left ventricular ischemia (>10%), transient ischemic dilation index (>1.07), and change in the left ventricular ejection fraction during stress (<2) (P = 0.0009). In patients with normal or slightly to moderately abnormal results on perfusion scans (<10% of left ventricular mass) during stress (n = 136), a preserved CFR (>1.93) excluded high-risk CAD with a high sensitivity (86%) and a high negative predictive value (97%). CONCLUSION: A normal CFR has a high negative predictive value for excluding high-risk CAD on angiography. Although an abnormal CFR increases the probability of significant obstructive CAD, it cannot reliably distinguish significant epicardial stenosis from nonobstructive, diffuse atherosclerosis or microvascular dysfunction.